MECHANISM FOR SETTLEMENT OF DEFAULT IN THE MORTGAGE LOAN AGREEMENT AT PT. BPR BKK PURWODADI GROBOGAN - Imron Chumaidi (Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine the mechanism for settling defaults in the imposition of credit contracts at PT. BPR BKK PURWO-DADI GROBOGAN and to understand the ideal default settlement mechanism in imposing credit contracts at PT. BPR BKK PURWODADI GROBOGAN. This research uses a sociological juridical approach, and the research specification is descriptive-analytical. The data used are primary data, secondary data is data obtained directly from the field using inter- views, and secondary data is library research. The results obtained: 1) If the Customer defaults in fulfilling his obligations in terms of installments or loan repayments, then settle the default against the Debtor, PT. BPR BKK PURWODADI GROBOGAN makes a settlement by conducting an auction at the KPKNL and completing the auction terms and Failure to Settle Dispute in Court 2). If the customer de- faults in fulfilling his obligations in terms of installments or repayments, the ideal default loan settlement mechanism in imposing credit agreements are by Settlement of Banking Disputes Through Mediation Forums, Warning Letters, Refinancing/Refreshing, Personal Guarantees, sale of assets/objects guarantee together.